A cognitive behavioural therapy smartphone app for adolescent depression and anxiety: co-design of ClearlyMe. (16th March 2022) - Li, S.H.; Achilles, M.R.; Spanos, S.; Habak, S.; Werner-Seidler, A.; O'Dea, B.
Abstract: Adolescence is associated with heightened vulnerability to symptoms of depression and anxiety. In-person and computerised cognitive behavioural therapy (CBT) are effective treatment options, yet uptake and engagement remain low. Smartphone delivery of CBT offers an alternative, highly accessible method of delivering CBT. However, there is no freely available CBT smartphone application (app) specifically designed to reduce depression and anxiety symptoms in adolescents. The aim of this study was to design a new CBT smartphone app (ClearlyMe) that targets depressive and anxiety symptoms in adolescents. We engaged in a rigorous co-design process with adolescents ( n =36), parents ( n =15), and mental health professionals ( n =32). Co-design involved: (1) discovery of users' needs, views and preferences by conducting focus groups, (2) defining app features through ideation workshops and user consultations, (3) designing therapeutic CBT content and visual features, and (4) testing prototypes. Users were involved at every step and the process was iterative, with findings carried forward to ensure continued refinement of concepts and features. We found a preference for vibrant, cheerful colours and illustrations and non-endorsement of gamification and chatbots, which contrasted with findings from other studies. Preferences were largely consistent between the three user groups. However, adolescents preferred an app that could be used autonomously without professional support, whereas mental health professionals desired a product for use as a therapy adjunct to support CBT skill development. The importance of co-design, and particularly the inclusion of all stakeholders throughout the entire co-design process, is discussed in relation to the design of ClearlyMe. Key learning aims: (1) To understand the co-design process that underpins the development of a new CBT smartphone app for youth with elevated symptoms of depression and anxiety. (2) To understand adolescent, parent and mental health professionals' key preferences regarding the features and functionality of a CBT smartphone app for adolescents with elevated symptoms of depression and anxiety. (3) To understand how ClearlyMe has been designed as both a therapy adjunct and stand-alone program, and how it can be incorporated into day-to-day clinical practice.